Determinants of the CmoB carboxymethyl transferase utilized for selective tRNA wobble modification. Issue 9 (8th April 2015) - Kim, Jungwook; Xiao, Hui; Koh, Junseock; Wang, Yikai; Bonanno, Jeffrey B.; Thomas, Keisha; Babbitt, Patricia C.; Brown, Shoshana; Lee, Young-Sam; Almo, Steven C.
Abstract: Enzyme-mediated modifications at the wobble position of tRNAs are essential for the translation of the genetic code. We report the genetic, biochemical and structural characterization of CmoB, the enzyme that recognizes the unique metabolite carboxy- S -adenosine-L-methionine (Cx-SAM) and catalyzes a carboxymethyl transfer reaction resulting in formation of 5-oxyacetyluridine at the wobble position of tRNAs. CmoB is distinctive in that it is the only known member of the SAM-dependent methyltransferase (SDMT) superfamily that utilizes a naturally occurring SAM analog as the alkyl donor to fulfill a biologically meaningful function. Biochemical and genetic studies define the in vitro and in vivo selectivity for Cx-SAM as alkyl donor over the vastly more abundant SAM. Complementary high-resolution structures of the apo- and Cx-SAM bound CmoB reveal the determinants responsible for this remarkable discrimination. Together, these studies provide mechanistic insight into the enzymatic and non-enzymatic feature of this alkyl transfer reaction which affords the broadened specificity required for tRNAs to recognize multiple synonymous codons.